Processing of flour from potato (Solanum Tubesorum, Linn. Var. Cosima) - Murillo, Cecilia F.
ABSTRACT A study was undertaken to develop a process for potato production. The study was divided into two phases: determination of more suitable variety of potato between Cosima and Red Pontiac and development of a procedure for potato flour production. In the first phase, Cosima was chosen as the better variety on the basis of physico-chemical test and was found to have a specific gravity of 1.0844, 18.54% total solids, 15.00% starch, 1.38% total sugars, and 0.39% reducing sugars. Red Pontiac had a specific gravity of 1.0385, % total solids of 17.17%, starch content of 14.24%, and total and reducing sugars of 2.58% and 0.73% respectively. Using the Cosima variety of potato in the second phase, it was found that 20 minutes of blanching in live steam was adequate. The blanched potatoes were sulfited by dipping in 0.2% Na₂S₂0₅ solution for one and two hours. One hour sulfiting was found better than two hours on the basis of SO₂ retention test, % yield of flour, sensory characteristics, and performance in bread. Flour from potato sulfited for one hour in 0.2% Na₂S₂0₅ solution was found to retain 186 ppm of SO₂ and had a yield 17.18% while that from potatoes sulfited for two hours had 365 ppm SO₂ and a yield of 18.25%. The bread made from potato sulfited for one hour had better characteristics with a large volume of 550 cc., weight of 265g., and density of 0.482 g/cc whereas the bread from flour with potato sulfited for two hours had a volume of 485 cc., weight of 260g., and density of 0.536 g/cc.